GUI development for DC motor application in MATLAB - Nazariha, Mat Salleh (2008)
The application of the DC motor in real life is very command. In industry, DC motor controls are very important to make the mechanical movement operation running. There are many applications that have been develop by using motor control in electronic field such as Computer Integral Manufacturing (CIM) and Flexible Manufacturing System (FMS). The objective of this project is to develop the Graphical User Interface of motor control and temperature sensor through MATLAB GUIDE, interface the MATLAB GUI consist transmit and receiver program with hardware via serial communication and control the DC motor and temperature sensor. The PIC is used to control DC motor and temperature sensor. By using MATLAB GUIDE, the process of laying out and programming GUIs and interface with PIC via serial communication port to control the DC motor and temperature sensor will be easier because it is already provides set of tools. As a result, the DC motor control and temperature sensor will consist transmit and receiver program is able to be controlled by using MATLAB GUI and interface the MATLAB GUI with PIC via serial communication port.